2011
DOI: 10.1002/aic.12284
|View full text |Cite
|
Sign up to set email alerts
|

A new framework and a simpler method for the development of batch crystallization recipes

Abstract: We use a new generalized dimensionless model of a seeded batch crystallization process to compare results from four crystal growth rate/concentration trajectories: a numerically-computed optimal trajectory, a constant growth rate trajectory, a trajectory proposed by Mullin and Nyvlt that can be calculated without a kinetic model, and a linear concentration-time trajectory. Because the model is generalized and dimensionless it is not specific to any particular solute-solvent system. We show that if seed propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 13 publications
1
31
0
Order By: Relevance
“…It does not depend on any kinetic parameters such as k g , k b , etc. Ward, et al showed that in almost all cases, this trajectory performs almost as well as the optimal trajectory at minimizing the nucleated mass.…”
Section: Commentsmentioning
confidence: 94%
See 4 more Smart Citations
“…It does not depend on any kinetic parameters such as k g , k b , etc. Ward, et al showed that in almost all cases, this trajectory performs almost as well as the optimal trajectory at minimizing the nucleated mass.…”
Section: Commentsmentioning
confidence: 94%
“…The initial seed crystal size distribution is parabolic (as discussed by Ward et al) with dimensionless width w ′ = 1, seed mean size x ′ 0 = 1.5, and dimensionless seed mass m ′ s = 0.1. The growth rate trajectory that minimized each objective function was determined using the simulated annealing toolbox in Matlab.…”
Section: Model Development and Optimizationmentioning
confidence: 99%
See 3 more Smart Citations